2022
DOI: 10.1093/chemse/bjac025
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual odor qualities predict successful odor identification in old age

Abstract: Odor identification is a common assessment of olfaction, and it is affected in a large number of diseases. Identification abilities decline with age, but little is known about whether there are perceptual odor features that can be used to predict identification. Here, we analyzed data from a large, population-based sample of 2,479 adults, aged 60 years or above, from the Swedish National study on Aging and Care in Kungsholmen. Participants performed both free and cued odor identification tests. In a separate e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 63 publications
1
2
0
Order By: Relevance
“…Children's olfactory preferences are varied though often food-related (as shown in our studies in Malawi, Mwenda Chinula, 2023 andNorway, Kucirkova andBruheim Jensen, 2023). Recent studies show similarities in children's olfactory perception across countries (Oleszkiewicz et al, 2022) and provide evidence for the predictive value of early odor perceptions for later life (Lindroos et al, 2022). The recent evidence is thus gradually strengthening the argument that children's olfactory perceptions, preferences and experiences need to be more intensively studied and stimulated.…”
Section: The Potential Role Of Olfactionsupporting
confidence: 74%
“…Children's olfactory preferences are varied though often food-related (as shown in our studies in Malawi, Mwenda Chinula, 2023 andNorway, Kucirkova andBruheim Jensen, 2023). Recent studies show similarities in children's olfactory perception across countries (Oleszkiewicz et al, 2022) and provide evidence for the predictive value of early odor perceptions for later life (Lindroos et al, 2022). The recent evidence is thus gradually strengthening the argument that children's olfactory perceptions, preferences and experiences need to be more intensively studied and stimulated.…”
Section: The Potential Role Of Olfactionsupporting
confidence: 74%
“…In the assessment of OI, higher cognitive processes such as olfactory memory, semantic understanding, and object naming are recruited [ 29 , 30 ]. Studies indicate that the perceived intensity of the odor is a predictor of higher order olfactory performance [ 31 ]. We found that both the OD and OI were significantly correlated with the MMSE score in the overall sample, whereas in patients with GPI, a correlation between the OD score and MMSE score was not detected.…”
Section: Discussionmentioning
confidence: 99%
“…49,128 Aging is accompanied by a decrease of sensory abilities, including smell and taste. 179,180 Such decrease does not appear to be linear, 181 but would instead correspond to different olfactory phenotypes, 182 and is further influenced by the environment. 31 Olfactory loss appears to start in the fifth decade of life in healthy humans 183 (Figure 2), although this evidence almost exclusively originates from studies of industrialized populations and may depend on the types of cumulative environmental exposures encountered through life.…”
Section: Later Lifementioning
confidence: 99%